Features of methods for investigating latent economic crimes - Рибікова, Ганна Володимирівна; Сучкова, Владлена Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article deals with such a phenomenon as «latent crime» in the economic sphere, its concept, types and ways of overcoming. Some methods, which are used in the process of study of latent economic crimes, are analyzed.